Respiratory Microbial Co-infection With SARS-CoV-2 - Massey, Bill W.; Jayathilake, Karuna; Meltzer, Herbert Y. (Frontiers in Microbiology, 2020)
The prevalence and types of respiratory pathogens in relation to age and domicile were determined in 12,075 US subjects tested for possible SARS-CoV-2 infection. The co-occurrence of infection with SARS-CoV-2 and other respiratory pathogens was related to race, gender, age, nursing home and outpatient status. Infections with other respiratory pathogens able to produce SARS-CoV-2 like symptoms were present in COVID-19 negative subjects and were more common in SARS-CoV-2 positive than negative subjects. Advanced age and nursing home status impacted co-infection rates as they do SARS-CoV-2 infection rates. Addressing co-pathogens is a necessary part of diagnosis and treating respiratory illness in the current SARS-CoV-2 pandemic.